Jewish Suffering in the French Legal Imagination from Vichy to the Fourth Republic - Dean, Carolyn J. (AJS review, 2025)
Laws passed under the Vichy regime in 1941 and revised in 1945 under the French provisional government (1944-1946) mandated the denunciation of crimes and penalized failures to rescue persons in peril. They became part of a body of continental law in postwar Europe regarding "duty to rescue" aimed at legislating the moral duties of citizens. This essay argues that the reception of the 1941 law illuminates how bystanders facilitated Jewish political exclusion under the Nazi Occupation. It also shows how the drafting of the 1945 law shaped Jewish inclusion in postwar France. The essay revisits debates about bystanders under Nazi Occupation and postwar French justice to make legible morally culpable acts whose effects are often as elusive to bystanders as they are palpable to Jewish victims. It shows how bystanders enable structural forms of discrimination to which they have no intentional or causal relation, but not by referencing passivity., Abstract:, Laws passed under the Vichy regime in 1941 and revised in 1945 under the French provisional government (1944-1946) mandated the denunciation of crimes and penalized failures to rescue persons in peril. They became part of a body of continental law in postwar Europe regarding "duty to rescue" aimed at legislating the moral duties of citizens. This essay argues that the reception of the 1941 law illuminates how bystanders facilitated Jewish political exclusion under the Nazi Occupation. It also shows how the drafting of the 1945 law shaped Jewish inclusion in postwar France. The essay revisits debates about bystanders under Nazi Occupation and postwar French justice to make legible morally culpable acts whose effects are often as elusive to bystanders as they are palpable to Jewish victims. It shows how bystanders enable structural forms of discrimination to which they have no intentional or causal relation, but not by referencing passivity.